Hotel feedback sentiment identifier using BERT - Medina Pauca, Walther Mauricio (2023)
The way of writing of the human being was changing over time being reduced/abbreviated by the new generations. The project will investigate these forms of writing of people through hotel comments, in order to identify and classify them according to whether it is a formal or informal comment; at the same time we will try to identify whether each of these has positive or negative information. All the processes to identify texts will be used with Natural Language Processing (NLP), so we will be able to identify different sentences according to the context that will be found in the comment database, which will be taken from TripAdvisor.